Transformation of fibroblast‐like synoviocytes in rheumatoid arthritis; from a friend to foe - Mousavi, Mohammad Javad (Auto Immun Highlights, 2021)
Swelling and the progressive destruction of articular cartilage are major characteristics of rheumatoid arthritis (RA), a systemic autoimmune disease that directly affects the synovial joints and often causes severe disability in the affected positions. Recent studies have shown that type B synoviocytes, which are also called fibroblast-like synoviocytes (FLSs), as the most commonly and chiefly resident cells, play a crucial role in early-onset and disease progression by producing various mediators. During the pathogenesis of RA, the FLSs’ phenotype is altered, and represent invasive behavior similar to that observed in tumor conditions. Modified and stressful microenvironment by FLSs leads to the recruitment of other immune cells and, eventually, pannus formation. The origins of this cancerous phenotype stem fundamentally from the significant metabolic changes in glucose, lipids, and oxygen metabolism pathways. Moreover, the genetic abnormalities and epigenetic alterations have recently been implicated in cancer-like behaviors of RA FLSs. In this review, we will focus on the mechanisms underlying the transformation of FLSs to a cancer-like phenotype during RA. A comprehensive understanding of these mechanisms may lead to devising more effective and targeted treatment strategies.